EFFECTIVENESS OF SELECTED NURSING STRATEGIES FOR GESTATIONAL DIABETES MELLITUS - D. ARULMOZHI,; DR. A.J. ASIRVATHAM,; DR. MANGALAGOWRI,; DR. S.J.NALINI,; DR. R. VIJAYARAGHAVAN, (International Journal of Pharma and Bio Sciences, 2015)
Gestational diabetes mellitus (GDM) was a perfect window of opportunity for the prevention of DM in two generations, and its incidence is increasing in our country. Awareness of the condition among antenatal women will translate into prevention and early diagnosis of the disease. This study was done to determine the awareness of GDM among all the antenatal women who attend a Primary Health Center (PHC) for antenatal care. One hundred and twenty antenatal women participated in the study. Mean age of the women was 23.8 years (SD: 2.94). Overall, 17.5% women had good knowledge, 56.7% had fair knowledge, and 25.8% women had poor knowledge about GDM. The major sources of awareness of GDM were reported to be television/radio, neighbors/friends, and family members. Only a small proportion of rural antenatal women had good knowledge about GDM. The awareness that untreated GDM may pose a risk to the unborn child was high among the study women. Health care workers have to play a greater role in bringing about awareness about GDM among antenatal women. Educating the primi antenatal mothers with GDM regarding the management of gestational diabetes mellitus will prevent the complications associated with GDM, also to reduce the neonatal & maternal mortality, morbidity rates.